GoZibil: Aplikasi Monitoring Tempat Pembuangan Sampah di Kelurahan Mangsang - Nasrullah, Muchamad Fajri Amirul; Failasuf, Banu; Nadeak, Kennedi Riado; Risma, Ellita Eka (JURNAL INTEGRASI, 2023)
Waste management is still the biggest problem in the country. Poor governance and lack of public awareness of environmental cleanliness cause waste to accumulate in the community. At present, waste management in the city of Batam is particularly the case with Mangsang Urban Vilage still using conventional garbage transportation systems where officers transport garbage once a week. Increasing population, garbage production will also increase. With the dense population causing waste management activities currently in use to be less effective, to help with this problem, there needs to be innovation in its handling. Therefore, the garbage transportation system requires an application that is integrated with IoT connected to the smartphone. The purpose of designing and building this application is to provide ease of managing waste where problems that have been difficult to overcome can be pressed like garbage accumulation, the difficulty of disposing of large sized garbage, the absence of complaints facilities, payment of ineffective cleaning fees, and lack of education in the community regarding waste can be overcome by innovation in this application. GoZibil The Garbage Handling Application can be used and has been tested using the black-box testing method to find out the functionality of the application that has been built.